Pengaruh Tegangan dan Laju Alir pada Pengolahan Limbah Cair Tahu Menjadi Air Bersih dengan Metode Elektrokoagulasi Secara Kontinyu - Idral Amri; Pratiwi Destinefa; Zultiniar (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2020)
The liquid waste of the tofu industry contains high organic contaminants, such as proteins and amino acids. These organic compounds causes liquid waste of tofu industry to contain high BOD, COD, and TSS so that it can pollute the environment. Therefore, tofu liquid should be removed first by electrocoagulation method. This method has the potential to purify tofu liquid waste and decrease the content of COD, BOD, TSS, and pH contained without the addition of coagulants. The purpose of this study was to determine the effect of voltage and flow rate to neutralize pH, and reduce levels of COD, BOD, and TSS in tofu liquid waste. The parameters tested included COD, BOD, TSS, and pH using a pH meter. The electrocoagulation process uses electrical power that flows in the direction of the electrode. The electrocoagulation reactor was paired with a cable connected to the power supply then connected to an electric current with voltage variations (8; 10; and 12 V) and variations in flow rates ((0.439 ; 0.243 ; 0.087 L/min). The results of this study found that optimum conditions were obtained at current of 12 V and flow rate of 0.087 L/min with increasing pH from pH from 3.5 to 67, a decreas in COD of 72.17% from 1017 mg/L to 283 mg/L , a decrease in BOD of 71.53% from 513 mg/L to 146 mg/L, a decrease in TSS of 90.90% from 1100 mg/L to 100 mg/L. The results of the research obtained are in accordance with the waste water quality standards by Permen LH No.5 2014.